Crizotinib targets in glioblastoma stem cells. (27th September 2017) - Junca, Audelaure; Villalva, Claire; Tachon, Gaëlle; Rivet, Pierre; Cortes, Ulrich; Guilloteau, Karline; Balbous, Anaïs; Godet, Julie; Wager, Michel; Karayan‐Tapon, Lucie
Abstract: Glioblastoma stem cells (GSCs) are believed to be involved in the mechanisms of tumor resistance, therapeutic failures, and recurrences after conventional glioblastoma therapy. Therefore, elimination of GSCs might be a prerequisite for the development of successful therapeutic strategies. ALK, ROS1, and MET are targeted by Crizotinib, a tyrosine kinase inhibitor which has been approved for treatment of ALK‐rearranged non–small‐cell lung cancer. In this study we investigated ALK, ROS1, and MET status in nine glioblastoma stem cell lines and tumors from which they arise. Fluorescent in situ hybridization (FISH), Sanger's direct sequencing, and immunohistochemistry were used to screen genomic rearrangements (or amplifications), genomic mutations, and protein expression, respectively. The immunohistochemical and FISH studies revealed no significant dysregulation of ROS1 in GSCs and associated tumors. Neither amplification nor polysomy of ALK was observed in GSC, but weak overexpression was detected by IHC in three of nine GSCs. Similarly, no MET amplification was found by FISH but three GSCs presented significant immunohistochemical staining. No ALK or MET mutation was found by Sanger's direct sequencing. In this study, we show no molecular rearrangement of ALK, ROS1, and MET that would lead us not to propose, as a valid strategy, the use of crizotinib to eradicate GSCs. However, MET was overexpressed in all GSCs with mesenchymal subtype and three GSCs presented an overexpression of ALK. Therefore, our study corroborates the idea that MET and ALK may assume a role in the tumorigenicity of GSC. Abstract : Tissue and stem cells microarrays from nine glioblastomas samples were used to evaluate expression and chromosomal abnormalities of ALK, ROS1, and MET. No molecular rearrangement of these three important genes was observed but rather an overexpression of ALK and MET in some of the glioblastoma stem cell samples, supporting the role of these two genes in tumorigenicity.